Be a hero save lives: the importance of first aid training / Mardiana Mazaulan, Noor Azila Azreen Md Radzi, and Muhamad Noor Mohamed - Mazaulan, Mardiana; Md Radzi, Noor Azila Azreen; Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Accidents do happen, make first aid as your best mate.” Mastering the essential first aid skills is paramount! Comprehensive first-aid training will equip you with the knowledge and skills to manage emergencies confidently. Learn CPR, first aid techniques, and more through a combination of theory, firsthand practice, and realistic simulations. The basis of first aid training needed is wound management, cardiopulmonary resuscitation (CPR), and the use of an automated external defibrillator (AED). The capacity to respond effectively in emergencies is a fundamental life skill [1]. Recognizing the critical importance of this ability, a first aid, CPR, and AED program was established to equip staff and students with the essential knowledge and practical skills necessary to manage medical emergencies.